Aphorpines and benzylisoquinoline alkaloids from bark of Cryptocarya crassinervia - Nurdin Saidi (Syiah Kuala University, 2011)
Two aphorpine alkaloids, (+)-lirinine 1 and (+)-lirioferine 2 and two bezylisoquinoline alkaloids (+)-reticuline 3 and (-)-N-Methylisococlaurine 4 were isolated from bark of Cryptocarya crassinervia. The structures were elucidated by spectral analysis, including 1D-NMR (1H, 13C, DEPT), 2D-NMR (COSY, HMQC, HMBC), UV, IR, and MS and comparison with the published data.